Special Autonomy and the Principles of Federal System: A Blurred Portrait of the Special Autonomy for Papua - Frans Reumi (Faculty of Law, Hasanuddin University, 2023)
The spirit of implementing decentralization and special autonomy contains the principle of federal arrangements is the right solution in the Indonesian government system. A unitary state in the form of a Republic with social conditions, multicultural society, and geographical conditions with thousands of islands is a challenge in realizing prosperity. This article is normative-legal research. The data used are primary legal materials obtained from relevant regulations and secondary legal materials obtained from various related literatures. The result shows that implementing the principle of the reserve of powers was to the region and direct election system for regional heads and deputy regional heads. Meanwhile, decentralization which leads to a federal system, has positive and negative effects on the implementation of the functions and objectives of the state, stated in the spirit of special autonomy. Both de facto and de jure, this legal policy reflects the principle of the federal system, which aims to maintain the integrity of the Unitary State of the Republic of Indonesia.